Silicon-carbon composite negative electrode material based on regenerated graphite and preparation method of silicon-carbon composite negative electrode material
Recycled graphite was obtained through pretreatment and extraction of hydrometallurgy, and silicon-carbon composite anode material was prepared by hydrothermal synthesis and ball milling, which solved the low specific capacity of the negative electrode material of lithium-ion battery and the existence of silicon material in the de-lithium de-embedding process. Problem, excellent cycle performance and rate performance are achieved.
Patent Information
- Application Number
- CN202411774834.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The specific capacity of the negative electrode material of the existing lithium-ion battery is relatively low, and the silicon material has volume changes, poor conductivity and unstable SEI film problems during the de-lithium de-embedding process, making it difficult to meet the needs of high-energy-density batteries.
Graphite is treated by pretreatment and extraction of hydrometallurgy processes to obtain regenerated graphite material, and nanosilicon and regenerated graphite are prepared into silicon-carbon composite anode material by hydrothermal synthesis and ball milling.
The excellent cycle performance and rate performance of silicon-carbon composite anode material are achieved, which can be better applied to lithium-ion batteries, reduce the cost of recycling processes, and provide good lithium storage capacity and site.
Smart Images

Figure CN119481014A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery negative electrode materials, and in particular to a silicon-carbon composite negative electrode material based on recycled graphite and a preparation method thereof. Background Art
[0002] With the development of human life and the gradual progress of society, people's excessive use of fossil energy makes the depletion of fossil energy inevitable. Fossil energy will produce greenhouse gases such as CO2 during use, leading to increasingly prominent environmental problems. Therefore, the development of clean and renewable energy is the direction of future development. As a renewable energy source, lithium-ion batteries are widely used in automobiles, electronic appliances and other fields due to their excellent electrochemical properties such as high energy density and long cycle life.
[0003] Graphite is the most effective negative electrode material in lithium-ion batteries. As lithium-ion batteries are widely used in electric vehicles and electronic devices, the number of waste lithium batteries has increased rapidly, resulting in a large amount of waste graphite. Recycling these waste graphites can not only avoid the environmental pollution problems caused by traditional landfill treatment methods, but also achieve the recycling of graphite, which is of great significance to saving mineral resources and ensuring the sustainable development of the new energy industry.
[0004] In addition, the theoretical specific capacity of graphite is only 372 mAh g -1 , which is difficult to meet the actual needs of high energy density batteries. Silicon has a high current density of up to 4200mA·g -1 Theoretical specific capacity and lower voltage platform (~0.4Vv.Li / Li + ), there is no risk of lithium deposition during lithium removal / insertion, and it is an ideal negative electrode material. However, there are some obstacles that limit the application of silicon materials as negative electrodes for lithium-ion batteries. This is mainly because silicon has huge volume changes, poor conductivity, and the formation of unstable SEI film during lithium removal / insertion.
[0005] In view of this, the present invention aims to propose a silicon-carbon composite negative electrode material based on recycled graphite and a preparation method thereof, so as to better solve the above technical problems. Summary of the invention
[0006] To solve the above problems, the present invention provides a silicon-carbon composite negative electrode material based on regenerated graphite and a preparation method thereof, wherein the graphite negative electrode material is treated by pretreatment and extraction hydrometallurgical processes, and then the regenerated graphite material is obtained by carbonization, and nano-silicon and regenerated graphite are prepared into a silicon-carbon composite negative electrode material by hydrothermal synthesis and ball milling.
[0007] The technical solution adopted by the present invention is:
[0008] A method for preparing a silicon-carbon composite negative electrode material based on regenerated graphite comprises the following preparation steps:
[0009] S1. The waste graphite is placed in an oven for drying, and after drying, it is taken out and ground into powder, named SG, SG is extracted with choline chloride-oxalic acid extractant, and the solid is separated by centrifugation, and the solid is dried to obtain regenerated graphite, named RG;
[0010] S2. Place nano-silicon and sugar in a reactor and perform ultrasonic treatment to mix the nano-silicon and sugar evenly. After ultrasonic treatment, place the reactor in an oven for hydrothermal reaction. After the hydrothermal reaction, rinse the product with ultrapure water and place it in a crucible. Then, place the crucible in a muffle furnace for annealing. After cooling, a silicon-carbon composite material can be obtained.
[0011] S3. Place the silicon-carbon composite material and regenerated graphite in a ball mill jar and mill them in a ball mill to obtain an active material, namely, a silicon-carbon composite negative electrode material based on regenerated graphite, named Si@C.
[0012] A further improvement to the above technical solution is that in step S2, the mass ratio of nano-silicon to sugar is 1 to 3:10.
[0013] A further improvement to the above technical solution is that in step S2, the sugar is glucose and / or starch.
[0014] A further improvement to the above technical solution is that in step S2, the ultrasonic treatment time is 0.5h to 2h.
[0015] A further improvement to the above technical solution is that in step S2, the hydrothermal reaction temperature is 100°C to 250°C, and the time is 5h to 12h.
[0016] A further improvement to the above technical solution is that in step S2, the temperature of the annealing treatment in the muffle furnace is 200° C. to 400° C., and the time is 2 h to 6 h.
[0017] A further improvement to the above technical solution is that in step S3, the mass ratio of the silicon-carbon composite material to the regenerated graphite is 1 to 2:1.
[0018] A further improvement to the above technical solution is that in step S3, the rotation speed of the ball mill is 400 r / min. -1 ~1000r·min -1 The ball milling time is 10h~25h.
[0019] Based on the same inventive concept, the present application also provides a silicon-carbon composite negative electrode material based on recycled graphite prepared using the above-mentioned preparation method.
[0020] The beneficial effects of the present invention are as follows:
[0021] The preparation method provided by the present invention processes graphite negative electrode materials through pretreatment and extraction hydrometallurgical processes, obtains regenerated graphite materials through carbonization, and prepares nano-silicon and regenerated graphite into silicon-carbon composite negative electrode materials through hydrothermal synthesis and ball milling methods. The extractant used in the present invention is green, low-toxic, environmentally friendly, and recyclable, which reduces the cost of the recycling process. At the same time, the elements such as N, P and S in the recycled graphite can not only provide lithium storage capacity, but also provide good sites for the combination of silicon-carbon materials, so that the finally prepared silicon-carbon composite negative electrode material has excellent cycle performance and rate performance, and can be better used as a negative electrode material in lithium batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 FT-IR graph of the regenerated graphite (RG) prepared in Example 1 of the present invention;
[0023] Figure 2 FT-IR graph of commercial graphite powder (CG);
[0024] Figure 3 XRD patterns of the regenerated graphite (RG) and commercial graphite powder (CG) prepared in Example 1 of the present invention;
[0025] Figure 4 The Si@C0.1 electrode prepared in Example 1 of the present invention is subjected to a current of 1000 mA·g -1 Cycle performance diagram of
[0026] Figure 5 The Si@C0.1 electrode prepared in Example 1 of the present invention is 1A·g- 1 To 6A·g -1 The rate performance diagram of
[0027] Figure 6 CV graph of the Si@C0.1 electrode prepared in Example 1 of the present invention;
[0028] Figure 7 is the Nyquist diagram of the Si@C0.1 electrode prepared in Example 1 of the present invention;
[0029] Figure 8 The Si@C0.2 electrode prepared in Example 2 of the present invention is subjected to a current of 1000 mA·g -1 Cycle performance diagram of
[0030] Fig. 9 The Si@C0.2 electrode prepared in Example 2 of the present invention is -1 To 6A·g -1 The rate performance diagram of
[0031] Fig.10 CV graph of the Si@C0.2 electrode prepared in Example 2 of the present invention;
[0032] Fig.11 is the Nyquist diagram of the Si@C0.2 electrode prepared in Example 2 of the present invention;
[0033] FIG. 12 is a TEM image of the Si@C0.2 electrode prepared in Example 2 of the present invention, wherein Figure 12-1 10nm, Figure 12-2 1nm;
[0034] Fig.13 This is an EDS element content diagram of the Si@C0.2 electrode prepared in Example 2 of the present invention;
[0035] FIG. 14 is an EDS element distribution diagram of the Si@C0.2 electrode prepared in Example 2 of the present invention, wherein Figure 14-1 is the C element, Figure 14-1 is the Si element, Figure 14-3 is the O element, Figure 14-4 is the P element;
[0036] Fig.15 The Si@C0.3 electrode prepared in Example 3 of the present invention is subjected to a current of 1000 mA·g -1 Cycle performance diagram of
[0037] Fig.16 The Si@C0.3 electrode prepared in Example 3 of the present invention is -1 To 6A·g -1 The rate performance diagram of
[0038] Fig.17 CV graph of the Si@C0.3 electrode prepared in Example 3 of the present invention;
[0039] Fig.18 This is the Nyquist diagram of the Si@C0.3 electrode prepared in Example 3 of the present invention. DETAILED DESCRIPTION
[0040] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively by way of examples, and preferred embodiments of the present invention are given below. However, the present invention can be implemented in a variety of different forms and is not limited to the embodiments described herein. Any other implementation schemes obtained by modifying or equivalently replacing the technical scheme of the present invention without creative results are within the protection scope of the present invention.
[0041] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for describing specific embodiments and are not intended to limit the present invention.
[0042] The numerical values disclosed in the embodiments of the present invention are approximate values, not definite values. When the error or experimental conditions permit, all values within the error range may be included without being limited to the specific numerical values disclosed in the embodiments of the present invention.
[0043] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0044] The following are specific embodiments of the present invention:
[0045] Example 1
[0046] The method for preparing a silicon-carbon composite negative electrode material based on regenerated graphite provided in this embodiment comprises the following steps:
[0047] S1: Preparation of recycled graphite
[0048] The waste graphite is placed in an oven for drying, and after drying, it is taken out and ground into powder, named SG, SG is extracted with choline chloride-oxalic acid extractant, and the solid is separated by centrifugation, and the solid is dried to obtain regenerated graphite, named RG;
[0049] S2: Preparation of silicon-carbon composite materials
[0050] After accurately weighing according to the mass ratio of nano-silicon to starch of 1:10, the mixture was placed in a reactor and subjected to ultrasonic treatment for 0.5 h to uniformly mix the nano-silicon and starch. After the ultrasonic treatment, the reactor was placed in an oven and subjected to hydrothermal synthesis reaction at 200°C for 10 h. After the hydrothermal synthesis reaction, the product was rinsed out with ultrapure water and placed in a crucible. The crucible was then placed in a muffle furnace and annealed at 300°C for 5 h. After cooling, a silicon-carbon composite material was obtained.
[0051] S3: Preparation of active substances
[0052] After being accurately weighed according to the mass ratio of silicon-carbon composite material to recycled graphite of 1:1, the mixture was placed in a ball mill and subjected to a grinding process at 400 r / min. -1 、600r·min -1 and 800r·min -1 The ball milling was carried out in a progressive speed cycle for 20 hours. After the ball milling was completed, the material was taken out to obtain a silicon-carbon composite negative electrode material based on regenerated graphite as an active material, which was named Si@C0.1.
[0053] The Si@C0.1 prepared in this example is prepared into a silicon-carbon negative electrode sheet
[0054] According to the mass ratio of active material (Si@C0.1): conductive carbon black: sodium carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) = 40:5:3:2, the corresponding mass of reagents are accurately weighed into a ball mill jar, and the jar is placed in a ball mill for ball milling. After the slurry is uniform, an automatic coater is used to evenly coat the slurry on the rough surface of a single-sided smooth copper foil. The coated product is placed in a vacuum drying oven for vacuum drying to obtain a silicon-carbon negative electrode sheet; the larger silicon-carbon negative electrode sheet is rolled and then cut into smaller electrodes using a slicer for loading into button batteries.
[0055] The above silicon-carbon negative electrode sheet is assembled into a battery
[0056] In the glove box, first place the silicon-carbon negative electrode sheet in the middle of the positive electrode shell, then drip an appropriate amount of electrolyte to soak the silicon-carbon negative electrode sheet, and then completely cover the diaphragm on the silicon-carbon negative electrode sheet, drip an appropriate amount of electrolyte again to soak the diaphragm, and then add lithium sheets, gaskets, springs, and negative electrode shells in turn, and after pressing, the CR2032 button lithium battery is obtained.
[0057] Example 2
[0058] The method for preparing a silicon-carbon composite negative electrode material based on regenerated graphite provided in this embodiment comprises the following steps:
[0059] S1: Preparation of recycled graphite
[0060] The waste graphite is placed in an oven for drying, and after drying, it is taken out and ground into powder, named SG, SG is extracted with choline chloride-oxalic acid extractant, and the solid is separated by centrifugation, and the solid is dried to obtain regenerated graphite, named RG;
[0061] S2: Preparation of silicon-carbon composite materials
[0062] After accurately weighing according to the mass ratio of nano-silicon to starch of 1:5, the mixture was placed in a reactor and subjected to ultrasonic treatment for 0.5 h to uniformly mix the nano-silicon and starch. After the ultrasonic treatment, the reactor was placed in an oven for hydrothermal reaction at 200° C. for 10 h. After the hydrothermal reaction, the product was rinsed out with ultrapure water and placed in a crucible. The crucible was then placed in a muffle furnace for annealing at 300° C. for 5 h. After cooling, a silicon-carbon composite material was obtained.
[0063] S3: Preparation of active substances
[0064] After being accurately weighed according to the mass ratio of silicon-carbon composite material to recycled graphite of 1:1, the mixture was placed in a ball mill and then placed in a ball mill at 400 r·min. -1 、600r·min -1 and 800r·min -1The ball mill is cyclically milled at a progressive speed for 20 hours. After the ball milling is completed, the material is taken out to obtain a silicon-carbon composite negative electrode material based on regenerated graphite as an active material, which is named Si@C0.2.
[0065] The Si@C0.2 prepared in this example is prepared into a silicon-carbon negative electrode sheet
[0066] According to the mass ratio of active material (Si@C0.2): conductive carbon black: sodium carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) = 40:5:3:2, the corresponding mass of reagents are accurately weighed into a ball mill jar, and the jar is placed in a ball mill for ball milling. After the slurry is uniform, an automatic coater is used to evenly coat the slurry on the rough surface of a single-sided smooth copper foil. The coated product is placed in a vacuum drying oven for vacuum drying to obtain a silicon-carbon negative electrode sheet; the larger silicon-carbon negative electrode sheet is rolled and then cut into smaller electrodes using a slicer for loading into button batteries.
[0067] The above silicon-carbon negative electrode sheet is assembled into a battery
[0068] In the glove box, first place the silicon-carbon negative electrode sheet in the middle of the positive electrode shell, then drip an appropriate amount of electrolyte to soak the silicon-carbon negative electrode sheet, and then completely cover the diaphragm on the silicon-carbon negative electrode sheet, drip an appropriate amount of electrolyte again to soak the diaphragm, and then add lithium sheets, gaskets, springs, and negative electrode shells in turn, and after pressing, the CR2032 button lithium battery is obtained.
[0069] Example 3
[0070] The method for preparing a silicon-carbon composite negative electrode material based on regenerated graphite provided in this embodiment comprises the following steps:
[0071] S1: Preparation of recycled graphite
[0072] The waste graphite is placed in an oven for drying, and after drying, it is taken out and ground into powder, named SG, SG is extracted with choline chloride-oxalic acid extractant, and the solid is separated by centrifugation, and the solid is dried to obtain regenerated graphite, named RG;
[0073] S2: Preparation of silicon-carbon composite materials
[0074] After accurately weighing according to the mass ratio of nano-silicon to starch of 3:10, the mixture was placed in a reactor and subjected to ultrasonic treatment for 0.5 h to mix the nano-silicon and starch evenly. After the ultrasonic treatment, the reactor was placed in an oven for hydrothermal reaction at 200°C for 10 h. After the hydrothermal synthesis reaction, the product was rinsed out with ultrapure water and placed in a crucible. The crucible was then placed in a muffle furnace for annealing at 300°C for 5 h. After cooling, a silicon-carbon composite material was obtained.
[0075] S3: Preparation of active substances
[0076] After being accurately weighed according to the mass ratio of silicon-carbon composite material to recycled graphite of 1:1, the mixture was placed in a ball mill and then placed in a ball mill at 400 r·min. -1 、600r·min -1 and 800r·min -1 The ball milling was carried out in a progressive speed cycle for 20 hours. After the ball milling was completed, the material was taken out to obtain a silicon-carbon composite negative electrode material based on regenerated graphite as an active material, which was named Si@C0.3.
[0077] The Si@C0.3 prepared in this example is prepared into a silicon-carbon negative electrode sheet
[0078] According to the mass ratio of active material (Si@C0.3): conductive carbon black: sodium carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) = 40:5:3:2, the corresponding mass of reagents are accurately weighed into a ball mill jar, and the jar is placed in a ball mill for ball milling. After the slurry is uniform, an automatic coater is used to evenly coat the slurry on the rough surface of a single-sided smooth copper foil. The coated product is placed in a vacuum drying oven for vacuum drying to obtain a silicon-carbon negative electrode sheet; the larger silicon-carbon negative electrode sheet is rolled and then cut into smaller electrodes using a slicer for loading into button batteries.
[0079] The above silicon-carbon negative electrode sheet is assembled into a battery
[0080] In the glove box, first place the silicon-carbon negative electrode sheet in the middle of the positive electrode shell, then drip an appropriate amount of electrolyte to soak the silicon-carbon negative electrode sheet, and then completely cover the diaphragm on the silicon-carbon negative electrode sheet, drip an appropriate amount of electrolyte again to soak the diaphragm, and then add lithium sheets, gaskets, springs, and negative electrode shells in turn, and after pressing, the CR2032 button lithium battery is obtained.
[0081] Performance Testing:
[0082] The regenerated graphite (RG) material prepared in Example 1 was characterized by FT-IR and XRD.
[0083] See also Figure 1 and Figure 2 It can be seen that compared with commercial graphite (CG), the regenerated graphite (RG) prepared in Example 1 of the present application has more surface functional groups, indicating that the regenerated graphite (RG) can provide more capacity contribution in terms of electrochemical performance.
[0084] See also Figure 3 As shown, the upper curve is recycled graphite (RG), and the lower curve is commercial graphite (CG). Figure 3 It can be seen that the characteristic peak intensity of carbon element in recycled graphite (RG) is sharper than that in commercial graphite (CG), indicating that it has a higher degree of graphitization.
[0085] from Figure 4-5 , Figure 8-9 and Figure 15-16 It can be seen that in terms of cycle performance and rate performance, the Si@C0.2 electrode performs better than both the Si@C0.1 electrode and the Si@C0.3 electrode.
[0086] from Figure 6-7 , Figure 10-11 and Figure 17-18 It can be seen that the Si@C0.1 electrode, Si@C0.2 electrode and Si@C0.3 electrode all have typical redox peaks in the range of 0.3V-0.6V, corresponding to the lithiation and delithiation processes of silicon respectively; Figure 7 , Fig.11 and Fig.18 From the Nyquist diagram, we can see that the charge transfer resistance R of the Si@C0.2 electrode after fitting ct It is 101.1Ω, which is smaller than that of Si@C0.1 electrode and Si@C0.3 electrode, indicating that it has smaller and better conductivity.
[0087] In the TEM image in FIG12 , lattice fringes (lattice gap of 0.31 nm) that can be clearly attributed to silicon can be observed; see Fig.13 The EDS element content diagram shows that the Si content in Si@C0.2 is as high as 36.63%, so it has a higher theoretical specific capacity; and the EDS element distribution diagram shown in Figure 14 shows that the surface of the Si particles is tightly coated with a layer of carbon elements.
[0088] In summary, the present invention prepares a silicon-carbon composite negative electrode material based on recycled graphite through pretreatment, extraction, hydrothermal synthesis and ball milling treatment, which can be better applied to lithium-ion batteries. The extractant in the present invention is choline chloride-oxalic acid, which is green, low-toxic, environmentally friendly, and recyclable, reducing the cost of the recycling process. At the same time, elements such as N, P and S in the recycled graphite can not only provide lithium storage capacity, but also provide good sites for the combination of silicon-carbon materials, so that the silicon-carbon composite negative electrode material prepared in the present invention has excellent cycle performance and rate performance, which can better meet application requirements.
[0089] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a silicon-carbon composite negative electrode material based on regenerated graphite, characterized in that: The method comprises the following preparation steps: S1. The waste graphite is placed in an oven for drying, and after drying, it is taken out and ground into powder, named SG, SG is extracted with choline chloride-oxalic acid extractant, and the solid is separated by centrifugation, and the solid is dried to obtain regenerated graphite, named RG; S2. Place nano-silicon and sugar in a reactor and perform ultrasonic treatment to mix the nano-silicon and sugar evenly. After ultrasonic treatment, place the reactor in an oven for hydrothermal reaction. After the hydrothermal reaction, rinse the product with ultrapure water and place it in a crucible. Then, place the crucible in a muffle furnace for annealing. After cooling, a silicon-carbon composite material can be obtained. S3. Place the silicon-carbon composite material and regenerated graphite in a ball mill jar and mill them in a ball mill to obtain an active material, namely, a silicon-carbon composite negative electrode material based on regenerated graphite, named Si@C.
2. The method for preparing a silicon-carbon composite negative electrode material based on regenerated graphite according to claim 1, characterized in that: In step S2, the mass ratio of nano-silicon to sugar is 1 to 3:
10.
3. The method for preparing a silicon-carbon composite negative electrode material based on recycled graphite according to claim 1, characterized in that: In step S2, the sugar is glucose and / or starch.
4. The method for preparing a silicon-carbon composite negative electrode material based on regenerated graphite according to claim 1, characterized in that: In step S2, the ultrasonic treatment time is 0.5h to 2h.
5. The method for preparing a silicon-carbon composite negative electrode material based on regenerated graphite according to claim 1, characterized in that: In step S2, the hydrothermal reaction temperature is 100°C to 250°C, and the time is 5h to 12h.
6. The method for preparing a silicon-carbon composite negative electrode material based on regenerated graphite according to claim 1, characterized in that: In step S2, the temperature of the annealing treatment in the muffle furnace is 200°C to 400°C, and the time is 2h to 6h.
7. The method for preparing a silicon-carbon composite negative electrode material based on recycled graphite according to claim 1, characterized in that: In step S3, the mass ratio of the silicon-carbon composite material to the regenerated graphite is 1-2:
1.
8. The method for preparing a silicon-carbon composite negative electrode material based on regenerated graphite according to claim 1, characterized in that: In step S3, the speed of the ball mill is 400 r / min. -1 ~1000r·min -1 The ball milling time is 10h~25h.
9. A silicon-carbon composite negative electrode material based on recycled graphite prepared by the preparation method according to any one of claims 1 to 8.